Perancangan Sistem Informasi Bengkel Online Berbasis Website Dengan PHP DAN MySQL - Rahady Puji Alfiansyah; Arafat Febriandirza (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
In automotive workshops, there are several stages of transactions that typically take place, including vehicle servicing, spare parts sales to customers, and spare parts purchases for workshop inventory. The lack of customer transaction records in automotive workshops poses difficulties in tracking the service history, customer database, and supplier information associated with customers. Additionally, the process of creating transaction receipts is still done manually, which is time-consuming, prone to errors in writing and cost calculations, and requires memorization of transaction lists. This research aims to develop and implement a web-based automotive workshop management system to enhance the efficiency of four-wheeler workshops and address the challenges they face. The system is developed using PHP programming language and MySQL database system. It facilitates data storage and provides ease in managing customer information, inventory, and transactions.